The effect of low dose ionizing radiation exposure on dynamic thiol-disulfide homeostasis and ischemia modified albumin levels: an observational study - Arıcan,Sule (2020)
Abstract Background: The primary objective of this study was to investigate the effect of low dose ionizing radiation exposure on thiol/disulfide homeostasis and ischemia modified albumin levels. The secondary objective is to compare thiol/disulfide homeostasis and ischemia modified albumin levels among the personnel exposed to low dose ionizing radiation in anesthesia application areas, in and out of the operation room. Methods: The study included a total of 90 volunteers aged between 18 and 65 years old, with 45 personnel working in a setting with potential for radiation exposure (Exposed Group) and 45 personnel in a setting without radiation exposure (Control Group). Their native thiol, total thiol, disulphide, albumine and IMA levels were measured. Exposed group included personnel who were exposed to radiation outside the operating room - Operation room (−) Group and inside the operating room - Operation room (+) Group. Results: Albumin, native and total thiol levels were significantly lower in the participants exposed to radiation in the anesthesia application area; no statistically significant difference was found in terms of disulfide and ischemia modified albumin levels. In the Operation room (−) Group exposed to radiation, native thiol and total thiol values were significantly lower compared to the Operation room (+) Group. Conclusion: Awareness of being in danger of oxidative stress should be established in personnel exposed to radiation in the anesthesia application area following low dose ionizing radiation exposure, and the necessary measures should be taken.